Transphobic Hate Crime - Jamel, Joanna (Palgrave Hate Studies, 2018)
This book uniquely combines a critical examination of the extent and diversity of transphobic hate crime together with a consideration of the victims and offenders. Trans people are marginalised in society and already negotiate complex physical and emotional challenges in order to live authentically in accordance with their self-identified gender presentation. Transphobic hate crime has devastating consequences both for the victim and trans people more generally by reinforcing the female/male binary and punishing gender non-conformity. In this thought-provoking study Jamel examines the history, extent, nature, and victim-offender relationship regarding these crimes whilst also considering the obstacles which affect legislation and policy-making decisions in response to hate crimes against trans people. The concept of a single transgender community is also critiqued in this book by exploring the diversity of trans identities cross-culturally. This original and timely book provides students, academics and those developing an interest in the topic with an understanding of the complexities of transphobic hate crime within the wider context of gender studies and critical criminology.